'I did not check if the teacher gave feedback': a qualitative analysis of Taiwanese postgraduate year 1 trainees' talk around e-portfolio feedback-seeking behaviours. Issue 1 (1st February 2019) - Fu, Ren-Huei; Cho, Yu-Hsueh; Quattri, Francesca; Monrouxe, Lynn V
Abstract : Objectives: Despite feedback being an extensively researched and essential component of teaching and learning, there is a paucity of research examining feedback within a medical education e-portfolio setting including feedback-seeking behaviours (FSBs). FSBs can be understood within a cost–value perspective. The objective of this research is to explore the factors that influence postgraduate year 1 (PGY1) trainee doctors' FSBs via e-portfolios. Setting: Postgraduate education provision in the largest teaching hospital in Taiwan. Participants: Seventy-one PGY1s (66% male). Methods: A qualitative semistructured one-to-one interview method was adopted. Interviews were audio recorded, transcribed verbatim, anonymised and checked for completeness. Data were analysed inductively via thematic framework analysis and deductively informed using FSB theory. The process comprised data familiarisation, identification of the themes, charting and data interpretation. Results: Two main themes of FSB related and e-portfolio related were identified. We present the theme focussing on FSB here to which n=32 (22 males, 10 females) of the n=71 participants contributed meaningfully. Subthemes include factors variously affecting PGY1s' positive and negative FSBs via e-portfolios at the individual, process and technological levels. These factors include learner-related (internal values vs social influence, forced reflection); teacher-related (committed educators vs superficial feedback); technology-related (face-saving vs lagging systems; inadequate user-interface) and process-related (delayed feedback, too frequent feedback) factors. Conclusions: Our findings reveal the complexity of PGY1s' FSBs in an e-portfolio context and the interaction of numerous facilitating and inhibiting factors. Further research is required to understand the range of facilitating and inhibiting factors involved in healthcare learners' FSBs across different learning, social, institutional and national cultural settings.